Regularización de la prescripción extraordinaria adquisitiva de dominio sobre bienes inmuebles con patrimonio familiar, en el código civil Ecuatoriano. - Castillo Ojeda, Alba Lucía Patricia (2012)
This research involves two legal institutions of our legislation, the Special Prescription Domain purchasing and Homestead, both with a transcendental and undeniable legal and social importance. Similarly, both prescription and heritage are intended to base their discussion, real estate. When there is actual possession of property, with the intention of lord or master, without violence, interruption or hiding and showing that this has happened over the last fifteen years, we can argue before a justice operator compliance with the law and therefore the right to own that property for "extraordinary prescription domain", as established in Section 2410 of the Civil Code, in addition, adverse possession is an original mode of acquiring ownership, based on the possession for a specified period of movable or immovable, which are in the human trade and therefore are prescriptive, according to Article 2398 of the Civil Code. If the actual possession of real property, which has met all requirements to be declared as such, falls on an asset that has "family assets" will not be possible to allege it as "extraordinary prescription domain" because of that property with heritage family has the purpose or purposes that lie outside the trade and apart from any action by creditors, and therefore a fundamental effect of family assets is that belonging to it are inalienable and indefeasible. The consultation theoretical and field research were conducted for this work have allowed me to expose foundation criteria and submit both the analysis and verification of the objectives and the testing of the hypothesis initially proposed, as well as expose the legal reform that I suggest be included in our legislation.